The future of influenza vaccines - Girard, Marc P. (Henry Stewart Talks, 2013)
Influenza virion structure, Available flu vaccines, Problems with current inactivated vaccines, Live attenuated vaccines, Subunit vaccine, New, recently licensed vaccines, Flu vaccines in development, Experimental vaccines, Issues with pandemic vaccines, Universal influenza vaccines, The HA protein